2018
DOI: 10.3390/diseases7010001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SMYD1 Results in Perinatal Lethality via Selective Defects within Myotonic Muscle Descendants

Abstract: SET and MYND Domain 1 (SMYD1) is a cardiac and skeletal muscle-specific, histone methyl transferase that is critical for both embryonic and adult heart development and function in both mice and men. We report here that skeletal muscle-specific, myogenin (myoG)-Cre-mediated conditional knockout (CKO) of Smyd1 results in perinatal death. As early as embryonic day 12.5, Smyd1 CKOs exhibit multiple skeletal muscle defects in proliferation, morphology, and gene expression. However, all myotonic descendants are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Vectors pBK-CMV-SMYD1A, pBK-CMV-SMYD1B, pBKCMV-SMYD1c and pBK-CMV-SMYD1B-YND-mutant were described previously ( Rasmussen et al., 2015 ; Rasmussen and Tucker, 2018 ). pSilencer5.1-U6-SMYD1-(sh-RNA), pSilencer5.1-U6-skNAC-(sh-RNA) and pSilencer5.1-U6-Scramble (sh-RNA) were generated with software (shRNA selector) available at http://hydra1.wistar (Upenn.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vectors pBK-CMV-SMYD1A, pBK-CMV-SMYD1B, pBKCMV-SMYD1c and pBK-CMV-SMYD1B-YND-mutant were described previously ( Rasmussen et al., 2015 ; Rasmussen and Tucker, 2018 ). pSilencer5.1-U6-SMYD1-(sh-RNA), pSilencer5.1-U6-skNAC-(sh-RNA) and pSilencer5.1-U6-Scramble (sh-RNA) were generated with software (shRNA selector) available at http://hydra1.wistar (Upenn.…”
Section: Methodsmentioning
confidence: 99%
“…SET and MYND Domain 1 (SMYD1) is a transcription factor characterized extensively in hematopoietic cells, cardiac/skeletal muscle (where it is essential for embryonic survival) ( Yahalom et al., 2018 ; Tracy et al., 2018 ; Franklin et al., 2016 ; Murayama et al., 2015 ; Rasmussen et al., 2015 ; Rasmussen and Tucker, 2018 ; Fujii et al., 2016 ; Hsia and Zon, 2005 ; Tan et al., 2006 ; Jing and Zon, 2011 ; Paik and Zon, 2010 ) and in endothelial cells where it acts as a SRF-interacting partner required for angiogenesis ( Ye et al., 2016 ). SMYD1 belongs to a family of three orthologous isoforms, SMYD1A (employed throughout this study and termed SMYD1), SMYD1B, and SMYD1C whose SET domains are split by a MYND protein-interaction domain [reviewed in ( Tracy et al., 2018 )].…”
Section: Introductionmentioning
confidence: 99%
“…SET and MYND domain containing 1 (Smyd1) is a histone methyltransferase specifically expressed in skeletal muscle and myocardium [ 7 , 8 , 9 ]. Smyd1 has been reported to play a crucial regulatory role in differentiation and maturation of skeletal and cardiac muscle cells [ 10 , 11 , 12 ], especially in sarcomere formation and assembly, muscle fibers composition, and myogenesis during cardiogenesis and ventricular development [ 13 ]; however, its role in the adult heart remains poorly understood. It was recently demonstrated that Smyd1 was significantly upregulated in a mouse model of pressure overload-induced HF and that cardiac-specific Smyd1 knockout mice developed cardiomyocyte hypertrophy that led to significant structural remodeling and severe HF [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its key role in cardiac and skeletal muscle development and regeneration ( Du et al., 2014 ), muscle-specific Smyd1 KO mice exhibited multiple defects of skeletal muscle, that finally led to perinatal death. Interestingly, trunk muscles were substituted with brown adipose tissue (BAT), and downregulation of key adaptive and innate immune transcription factors for BAT development and functionality, such as Il-6, TNFα, chemokine (C–C motif) ligand 6 ( Ccl6 ), chemokine (C–C motif) ligand 7 ( Ccl7 ), chemokine (C–C motif) ligand 9 ( Ccl9 ), forkhead box P3 ( Foxp3 ), BAF chromatin remodelling complex subunit BCL11A (Bcl11A), RUNX family transcription factor 1 ( RunX1 ) and core binding factor β (Cbfβ) , was observed ( Rasmussen and Tucker 2018 ). Furthermore, whole-genome resequencing of yak populations ( Bos grunniens, ruminant animals that are evolutionarily adapted to high altitudes and, therefore, hypoxia) identified copy number variations in SMYD1 , which may be involved in immune responses, as well as hypoxia adaptation ( Wang et al., 2019 ).…”
Section: Smyd1 and Immune Responses In Other Biological Contextsmentioning
confidence: 99%